Analisis Validitas Prediksibilitas Ujian Masuk Terhadap Hasil Belajar Satu Tahun Kedepan Di Mts Ali Maksum - Laelatul Badriah (LITERASI (Jurnal Ilmu Pendidikan), 2013)
Improving student learning outcomes can be known through examination or evaluation of student learning outcomes, as well as to improve the quality of education at a particular Islamic Junior Secondary School (MTs) Ali Maksum that can be seen through the entrance test the institution itself. Entrance test could be determine the quality of student learning outcomes, therefore it is very important be re-examined or entrance test kits that is used to determine the graduation of new students. Entrance tests can also determine the outcome of the first year students in the first and second semester. In this case retesting can be done by looking at the results of the entrance test, the results of the 1st semester final exam, and the results of the final exams 2 that is analyzed using multiple regression. This analysis is used to predict the results of the entrance test and see how much influence the results of the 1st semester final exams and final exams 2. From the discussion, it is a result of its high predictive significance between entrance exams, final exams 1, 2 and semester exams in the first year in MTs Ali Maksum. Keywords : Entrance test, predictabilities, validity